Vibrational Analysis of Heavy Metal-Nucleotide Interactions - SENTHIL, K.; IYANDURAI, N.; SAROJINI, R. (Asian Journal of Chemistry, 2010)
The interaction of Co2+ and Pd2+ with deoxyguanosine 5'-monophosphate (dGMP) in an aqueous solution at neutral pH with cation/ dGMP molar ratios (r) 1/5 and 1 was characterized by FT-Raman spectroscopy. Spectroscopic results show the formation of several types of cationdGMP complexes. Heavy metal perturbation of the phosphodioxy band at 1091 cm-1 is higher for Pd2+ than for Co2+. The spectral changes observed for the phosphodiester vibrations show that more than 50 % of the backbone geometry is eliminated in Co2+ and 100 % in case of Pd2+. In Co-dGMP complex, the glycosyl bond shows more flexibility, whereas in presence of Pd2+ ion, the guanine nucleoside exhibits both C2'-endo/anti and C3'-endo/syn conformation. Both the ions have strong affinity for the guanine base and the effect is more pronounced in the presence of Pd2+ ions.